Desenho : diálogos étnicos e culturais com crianças Guarani - Gama, Renata Lúcia de Assis (2011)
This research investigates children's drawings in Guarani, their relationships with their natural and cultural environment, seeking the same look on your own universe, so we know aspects of their customs and traditions. To this end we conducted a qualitative research, ethnographic, school Guarani indigenous municipality of Aracruz (Espírito Santo), with classes from 1st to 5th year of elementary school. Were discussed theories about children's drawing from the works of Iavelberg, Brent Wilson, Cola, among other authors who consider the design as a cultural product of a given society. The collected data were analyzed based on semiotics greimasiana, with emphasis in the plan of expression and content.